ANALISIS BUKU AJAR TENDANCES A1 - LIVRE DE L'ÉLÈVE - Zahra, Fatma Az (2017)
Textbook has an important role in learning foreign languages. Analyzing textbook is needed in order to select the textbook which is in line with both students' and teachers' needs. Tendances A1 - Livre de l'élève is the newest French textbook published in 2016; therefore, a study was conducted to analyze the textbook. The study is aimed at finding out the structures, language aspects, advantages and disadvantages of the textbook. The descriptive study applies the qualitative method. Based on the result of the study, it is found out that Tendances A1 - Livre de l'élève is divided into six sections, that is, introduction, tableau des contenus, mode d'emploi, unité, leçon, dan annexes. introduction, tableau des contenus, mode d'emploi, unité, leçon, dan annexes. The learning material of vocabulary is found in Réfléchissons... and Outils rubrics, that of phonetics and phonology learning in special phonetics rubric, that of structure in Réfléchissons... and Outils rubrics. Besides, there is a variety of exercises such as exercices à trous, questionnaires à choix multiples, exercices vrai ou faux, dan exercices d'association. The advantages of the textbook are as follow: it is completed with lots of interesting colourful pictures and photographs that can arouse students' interest in learning French, vocabulary learning is included in exercises, not in the form of list, it teaches different phonemes to débutant level (beginner students), it presents staged materials of verb and subject conjugation, it is condensed with exercses, it demands active participation of the students, it applies action-based teaching characterized with a final project that has to be completed by the students at the end of the unit, it is provided with livre de professeur (guide pédagogique), it is written by a group of experts, and it is cheaper than other French textbooks. Meanwhile, the disadvantage of the textbook is that it does not provide not only the evaluation in the form of questionnaires, portfolios, or auto-evaluation tables, but also special preparation exercises for DELF A1.---- Buku ajar berperan penting dalam pembelajaran, termasuk bahasa asing. Oleh karena itu, perlu adanya analisis buku ajar agar dapat memilih buku ajar yang sesuai dengan kebutuhan pengajar maupun pembelajar. Buku ajar yang dianalisis pada penelitian ini adalah Tendances A1 - Livre de l'élève yang merupakan buku ajar bahasa Perancis terbaru yang terbit pada tahun 2016. Tujuan dari penelitian ini untuk mengetahui struktur, aspek kebahasaan, kelebihan, dan kekurangan buku ajar yang dimaksud. Hasil penelitian menunjukkan bahwa buku ajar tersebut terbagi ke dalam beberapa bagian, yaitu introduction, tableau des contenus, mode d'emploi, unités, leçons, dan annexes. Pembelajaran kosakata, fonetik dan fonologi, dan tata bahasa terdapat pada rubrik Réfléchissons..., Outils, dan rubrik khusus fonetik. Terdapat pula variasi bentuk latihan seperti exercices à trous, questionnaires à choix multiples, exercices vrai ou faux, dan exercices d'association. Kelebihan buku ajar tersebut yaitu : terdapat banyak gambar dan foto menarik dan berwarna yang dapat menambah minat pembelajar untuk belajar bahasa Perancis, pembelajaran kosakata tergabung langsung dalam soal latihan dan tidak berbentuk list, mengajarkan perbedaan fonem pada pembelajar tingkat pemula, menyajikan materi konjugasi kata kerja dengan subjek yang bertahap, padat akan soal latihan, menuntut partisipasi aktif pembelajar, menggunakan pendekatan pengajaran berbasis tindakan (approche actionnelle) yang ditandai oleh adanya projet à atteindre (tugas akhir) yang harus dicapai oleh pembelajar pada akhir unité, dilengkapi dengan livre de professeur (guide pédagogique), ditulis oleh para ahli yang berpengalaman, dan memiliki harga yang murah. Kekurangan buku ajar tersebut yakni tidak menyediakan evaluasi berupa kuesioner, portofolio, atau tabel auto-evaluasi, juga latihan persiapan khusus untuk DELF A1.